The Biology and Pathobiology of Glutamatergic, Cholinergic, and Dopaminergic Signaling in the Aging Brain - Gasiorowska, Anna; Wydrych, Malgorzata; Drapich, Patrycja; Zadrozny, Maciej; Steczkowska, Marta; Niewiadomski, Wiktor; Niewiadomska, Grazyna (Frontiers in Aging Neuroscience, 2021)
The elderly population is growing worldwide, with important health and socioeconomic implications. Clinical and experimental studies on aging have uncovered numerous changes in the brain, including decreased neurogenesis, increased synaptic defects, greater metabolic stress, and enhanced inflammation. These changes are associated with cognitive decline and neurobehavioral deficits. Although aging is not a disease, it is a significant risk factor for functional worsening, affective impairment, disease exaggeration, dementia, and general disease susceptibility. Conversely, life events related to mental stress and trauma can also lead to accelerated age-associated disorders and dementia. Here we review human studies and studies on mice and rats, including those modeling human neurodegenerative diseases, that have helped elucidate (1) the dynamics and mechanisms underlying the biological and pathological ageing of the main projecting systems in the brain (glutamatergic, cholinergic, and dopaminergic) and (2) the effect of defective glutamatergic, cholinergic, and dopaminergic projection on disabilities associated with aging and neurodegenerative disorders like Alzheimer’s and Parkinson’s diseases. Detailed knowledge of the mechanisms of age-related diseases can be an important element in the development of effective ways of treatment. In this context, we briefly analyze which adverse changes associated with neurodegenerative diseases in the cholinergic, glutamatergic, and dopaminergic systems could be targeted by therapeutic strategies as a result our improved knowledge of these damaging mechanisms.